Pulmonary artery wave intensity analysis in pulmonary hypertension associated with heart failure and reduced left ventricular ejection fraction - Ivan H. W. Yim; Kim H. Parker; Nigel E. Drury; Hoong Sern Lim (Pulmonary Circulation, 2024)
Abstract Wave intensity analysis (WIA) uses simultaneous changes in pressure and flow velocity to determine wave energy, type, and timing of traveling waves in the circulation. In this study, we characterized wave propagation in the pulmonary artery in patients with pulmonary hypertension associated with left‐sided heart disease (PHLHD) and the effects of dobutamine. During right heart catheterization, pressure and velocity data were acquired using a dual‐tipped pressure and Doppler flow sensor wire (Combowire; Phillips Volcano), and processed offline using customized Matlab software (MathWorks). Patients with low cardiac output underwent dobutamine challenge. Twenty patients with PHLHD (all heart failure with reduced left ventricular ejection fraction) were studied. Right ventricular systole produced a forward compression wave (FCW), followed by a forward decompression wave (FDW) during diastole. Wave reflection manifesting as backward compression wave (BCW) following the FCW was observed in 14 patients. Compared to patients without BCW, patients with BCW had higher mean pulmonary artery pressure (28.7 ±  6.12 vs. 38.6 ± 6.5 mmHg, p = 0.005), and lower pulmonary arterial capacitance (PAC: 2.88 ± 1.75 vs. 1.73 ± 1.16, p = 0.002). Pulmonary vascular resistance was comparable. Mean pulmonary artery pressure of 34.5 mmHg (area under the curve [AUC]: 0.881) and PAC of 2.29 mL/mmHg (AUC: 0.833) predicted BCW. The magnitude of the FCW increased with dobutamine (n = 11) and correlated with pulmonary artery wedge pressure. Wave reflection in PHLHD is more likely at higher pulmonary artery pressures and lower PAC and the magnitude of reflected waves correlated with pulmonary artery wedge pressure. Dobutamine increased FCW but did not affect wave reflection.